GluN1 hypomorph mice exhibit wide-ranging behavioral alterations - Barkus, C; Dawson, L; Sharp, T; Bannerman, D (2012)
The psychotomimetic effects of N-methyl-d-aspartate receptor (NMDA) antagonists such as ketamine and phencyclidine suggest a role for reduced NMDA receptor-mediated neurotransmission in schizophrenia. GluN1 'hypomorph' (GluN1 hypo) mice exhibit reduced NMDA receptor expression and have been suggested as a mouse model of schizophrenia. However, NMDA receptors are ubiquitous and are implicated in many physiological and pathological processes. The GluN1 hypo mice have a global reduction of NMDA receptors and the consequences of such a global manipulation are likely to be wide-ranging. We therefore assessed GluN1 hypo mice on a battery of behavioral tests, including tests of naturalistic behaviors, anxiety and cognition. GluN1 hypo mice exhibited impairments on all tests of cognition that we employed, as well as reduced engagement in naturalistic behaviors, including nesting and burrowing. Behavioral deficits were present in both spatial and non-spatial domains, and included deficits on both short- and long-term memory tasks. Results from anxiety tests did not give a clear overall picture. This may be the result of confounds such as the profound hyperactivity seen in GluN1 hypo mice, although hyperactivity cannot account for all of the results obtained. When viewed against this background of far-reaching behavioral abnormalities, the specificity of any one behavioral deficit is inevitably called into question. Indeed, the present data from GluN1 hypo mice are indicative of a global impairment rather than any specific disease. The deficits seen go beyond what one would expect from a mouse model of schizophrenia, thus questioning their utility as a selective model of this disease. © 2012 The Authors. Genes, Brain and Behavior © 2012 Blackwell Publishing Ltd and International Behavioural and Neural Genetics Society.